TRENDS IN IMPLEMENTATION OF GAME USE AS LEARNING AT PRIMARY SCHOOLS LEVEL IN SCOPUS DATABASE: A BIBLIOMETRIC ANALYSIS - Atika Miftah Ramadhani; Nur Yusra Binti Yakob; Rizki Tika Ayuni; Zafrullah Zafrullah; Lovieanta ArrizaNur Yusra Binti Y; Anugrah Arya Bakti (Jurnal Penyelidikan Sains Sosial, 2024)
This research aims to look at research trends on gaming topics in primary schools. Researchers used 293 Scopus Database documents which had been selected using the PRISMA method. The data analysis technique used is bibliometric analysis using RStudio and Vosviewer. From the results of the analysis that has been carried out, it can be concluded that this research starts from 1978 to 2024, which has increased sixfold since the last 12 years. The peak of publication activity occurred in 2020, where there were 35 publications with 489 citations, and an h-index of 12. University of Turku from Finland was the best affiliate with 25 publications. Erno Lehtinen from the University of Turku, was the best author with an h-index of 4. Computers and Education was the best source with an h-index of 8. Tüzün et al. (2009) stands out as the document with the highest total citations, reaching 410 citations. 46 keywords were obtained which were divided into 6 clusters, with the keywords "Computational Thinking" and "Traditional Games" being keywords that could be used as recommendations in conducting further research in the field of Games in Primary Schools.